(3GdeJbf aj COH GdCWaGd hGdTHGH (B:s (3dWdGH GdJQHjI hOhQ GdeYdejf (B/s - (3HbGYj, EjeGf s 1960-; (3bHjYI, QGJH CMeOs ((3HjQhJ (B- (3dHfGf (B:s (3OGQ GdQGJH GdLGeYjI ,s, 2000)
(3jYGdL bVGjG GdbUI(B-(3GdTYQ(B-(3GdeSQM(B-(3GdJdaRjhf(B-(3GdEPGYI hGdEYdGf aj COH GdCWaGd hGdTHGH(B.s
(3HHdjhLQGajI (B: (3UaMI (B373-386.s
(3ehLg dWdGH GdJQHjI hOhQ GdeYdejf(B.s
Keywords: (3COH GdCWaGds -- (3OQGSI hJYdje (B((3YGdj(B)s